Characteristics of laminated flooring materials - Wong, L.G (Universiti Malaysia Sarawak, UNIMAS, 2009)
In this study, the surface and moisture characteristics of commercially manufactured laminated floorings and engineered hardwood floorings were evaluated. The influences of outdoor exposure on surface quality of the samples ranging from 1 week to 3 weeks were determined using Stylus technique. In additional, the influences of the indoor moisture conditions on the surface roughness, absorption rate and swelling thickness of the samples soaked from 2 hours to 15 days were investigated. Two roughness parameters, average roughness Ra and maximum roughness Rmax, calculated from the surface profiles of the samples employing a profilometer were used for the analyses. The samples have higher Ra and Rmax values when the Stylus tip traversed across the grain compared to along the grain. Statistically, a significant difference existed between laminated and engineered hardwood floorings. As a result, the engineered hardwood showed higher values for the outdoor and indoor tests compared to laminated flooring in terms of Ra, Rmax, moisture absorption rate and swelling thickness. The experimental result also proven the influence of moisture have higher tendency damaging the flooring samples compared to the influence of environment. Throughout the experiment, engineered hardwood samples degraded the most. This is because they are prone to moisture and weathering damages. The experimental results also showed laminated flooring samples have better surface quality, higher moisture resistance and are more durable. It was concluded that the laminated and engineered hardwood floorings is only limited for interior installation except for bathrooms. Laminated flooring is suitable to be used for the damp places such as kitchen, dining rooms and vicinity nearby the bathrooms which have higher tendencies exposed to the moisture. For engineered hardwood, the applications only limited to interior parts with the lowest moisture exposure such as living room, bedrooms, and staircase.